Molecular and morphological evidence reveals that Daimio Murray, 1875 is a junior synonym of Tagiades Hübner, 1819 (Lepidoptera: Hesperiidae: Tagiadini) - Huang, Zhen-Fu; Chiba, Hideyuki; Deng, Xiao-Hua; Huang, Si-Yao; Wang, Min; Fan, Xiao-Ling (Zootaxa, 2020)
Previous studies have shown that the genus Tagiades Hübner, 1819 is paraphyletic with regard to Daimio Murray, 1875 and/or Darpa Moore, 1866. In this study, we attempt to disentangle the relationships among these three genera based on an integrative approach including molecular data, morphological characters, and biological data from available sources. All evidence shows that Daimio and Tagiades are congeneric, isolated from Darpa. According to the rule of priority, Daimio (syn. n.) is a junior synonym of Tagiades. Therefore, we subsume tethys under Tagiades as Tagiades tethys (Ménétriés, 1875), comb. n.